2017
DOI: 10.1016/j.nicl.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical brain difference of subthreshold depression in young and middle-aged individuals

Abstract: BackgroundSubthreshold depression (StD) is associated with substantial functional impairments due to depressive symptoms that do not fully meet the diagnosis of major depressive disorder (MDD). Its high incidence in the general population and debilitating symptoms has recently put it at the forefront of mood disorder research.AimIn this study we investigated common volumetric brain changes in both young and middle-aged StD patients.MethodsTwo cohorts of StD patients, young and middle-aged, (n = 57) and matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 65 publications
(73 reference statements)
2
24
0
Order By: Relevance
“…A post-mortem study has demonstrated that patients with major depression had more neurons in the thalamic nuclei compared with control samples (Young et al, 2004 ). Our data showed that the susceptibility significantly increased in the left thalamus, which corroborated previous MR results that described the presence of structural abnormalities in the left thalamus among patients with depression (Lu et al, 2016 ; Li et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…A post-mortem study has demonstrated that patients with major depression had more neurons in the thalamic nuclei compared with control samples (Young et al, 2004 ). Our data showed that the susceptibility significantly increased in the left thalamus, which corroborated previous MR results that described the presence of structural abnormalities in the left thalamus among patients with depression (Lu et al, 2016 ; Li et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…While not studies of self-schemas, sMRI has been used to study associations between grey matter volume (GMV) and depression. Overall, clinically depressed adults and youth show reduced GMV in distributed regions including PFC, anterior cingulate cortex (ACC), amygdala, and hippocampus (see meta-analyses Arnone et al, 2016 , Bora et al, 2012 , Lai, 2013 , Peng et al, 2016 , Sacher et al, 2012 , Schmaal et al, 2017 ), although inconsistent findings have also been reported, potentially due to the heterogeneity of the depressed participants used in past work (e.g., treatment status; Amico et al, 2011 , Besteher et al, 2019 , Li et al, 2015 , Li et al, 2017 , Merz et al, 2018 ). In non-depressed youth, subthreshold depressive symptoms were associated with smaller GMV in vmPFC, ACC, and caudates ( Boes et al, 2008 , Vulser et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In brain imaging technology, voxel-based morphometry (VBM) can reflect the cortical volume density of the brain areas 16 , and resting-state fMRI (rs-fMRI) can reflect the functional connectivity (FC) of the brain network 17 , Both are useful methods to study the brain response of PSD. Seed-based analyses are frequently applied to resting-state data.…”
Section: Introductionmentioning
confidence: 99%